2020
DOI: 10.3389/fmicb.2020.584742
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Stage Changes in Early-Life Colonization and Acquisition of the Gut Microbiota and Its Correlations With Volatile Fatty Acids in Goat Kids

Abstract: In livestock, a comprehensive understanding of the early-life establishment and acquisition of commensal gut microbiota allow us to develop better husbandry management operations and manipulate the gut microbiota for young animals, improving the efficiency of animal production. Here, we collected 123 microbial samples of 11 healthy goat kids and their mothers to investigate the colonization and acquisition of the gut microbiota and their correlations with volatile fatty acids (VFAs) in goat kids from birth to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 98 publications
11
15
0
Order By: Relevance
“…Rumen pH is essential for rumen development, rumen environment, and even lamb health. The ruminal pH of lambs has been reported to be lower than that of adult sheep ( 59 ), which is similar to our present results. The lambs in the present study showed no signs of metabolic disorders, suggesting that lambs at this age tolerate pH levels that would be detrimental to the health of adult sheep.…”
Section: Discussionsupporting
confidence: 92%
“…Rumen pH is essential for rumen development, rumen environment, and even lamb health. The ruminal pH of lambs has been reported to be lower than that of adult sheep ( 59 ), which is similar to our present results. The lambs in the present study showed no signs of metabolic disorders, suggesting that lambs at this age tolerate pH levels that would be detrimental to the health of adult sheep.…”
Section: Discussionsupporting
confidence: 92%
“…We found that adding FHTR to the diet had no adverse effect on the alpha structures of fecal microorganisms and did not change the dominant phylum of the fecal microbiota. At the phylum level, the dominant bacteria were Bacteroides and Firmicutes, which is consistent with previous research [28,29]. The relative abundance of Phascolarctobacterium notably increased in the L15 group compared with the other groups.…”
Section: Fecal Microbiotasupporting
confidence: 91%
“…Recent studies have demonstrated that gut microbial structure abnormalities are associated with mental disorders, intestinal, metabolic, and other diseases (Dinleyici et al 2018;Qin et al 2012;Fung et al 2017;Valles-Colomer et al 2019). Moreover, various intrinsic and extrinsic factors such as host genetics (Fan et al 2021), genetic background (Korach-Rechtman et al 2019), diet (Wang et al 2019), age (O'Toole et al 2015;Guo et al 2020a), seasonal change (Peddada 2017), and habitat environment (Barelli et al 2020;Xiong et al 2021) greatly affect gut microbial community structure.…”
Section: Introductionmentioning
confidence: 99%